New numerical strategy to calculate normal depth in Rectangular channels (2016)
Review, analysis and comparison of explicit and implicit methods of recent development (2009-2015) for the calculation of normal depth in rectangular channels are performed; an adaptation of Newton Raphson method is developed as an alternative calculation of the problem and formulate a new method (called non-orthogonal directions NOD) is presented, this method is based on the modification of the fixed-point iteration method which is recognized for being simple but divergent with application limitations and restrictions. The proposed method determines the start value for the normal depth wisely, its formulation is simple, it has fast convergence and low computational cost that make it competitive with recognized and widely used methods (for example, Newton Raphson) as evidenced by the findings. © 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.